Methods and policies of the distribution of footwear in South Africa - Lipschitz, Gustav (Rhodes University, Faculty of Commerce, Department of Economics, 1947)
This thesis is mainly based on information obtained by discussion with footwear manufacturers, wholesale merchants, retailers and many other business men who were thoroughly acquainted with merchandising methods and policies. Many thanks to all those who assisted. Government Blue Books, other published and unpublished Reports and Economic and Trade journals were consulted wherever possible.
Keywords: Uncatalogued